2019
DOI: 10.1111/joim.12973
|View full text |Cite
|
Sign up to set email alerts
|

The value of bronchoalveolar lavage for discrimination between healthy and diseased individuals

Abstract: BackgroundBronchoalveolar lavage (BAL) is standard diagnostic procedure. Procedural recommendations have been made by pneumological societies including normal values for interpretation of BAL cytology. These normal values derive from small studies in healthy volunteers and have never been analysed for their sensitivity and specificity.ObjectivesThis study aims to analyse sensitivity and specificity of these normal values by assessing lavage cell composition in healthy and diseased individuals.MethodsMore than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
7
0
2
Order By: Relevance
“…Therefore, we used the same bacterial solution in three independent gradient centrifugation runs and plated 5 μl of each centrifugation sample on each three independent plates before and after isolation and calculated the yield (see Table 1). The number of bacteria in this test run was 5.7 × 10 3 CFU/ml, below the average bacterial load of a BAL sample of 7 × 10 4 CFU/ml [26,27]. Therefore, if an acceptable yield is possible with such a low bacterial load, this method can also be used for samples with higher concentrations.…”
Section: Quality Control Of the Isolation Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, we used the same bacterial solution in three independent gradient centrifugation runs and plated 5 μl of each centrifugation sample on each three independent plates before and after isolation and calculated the yield (see Table 1). The number of bacteria in this test run was 5.7 × 10 3 CFU/ml, below the average bacterial load of a BAL sample of 7 × 10 4 CFU/ml [26,27]. Therefore, if an acceptable yield is possible with such a low bacterial load, this method can also be used for samples with higher concentrations.…”
Section: Quality Control Of the Isolation Methodsmentioning
confidence: 81%
“…Moreover, there are also very few bacteria in a BAL sample, and this amount also varies between individual patients. On average, BAL fluid contains 7 × 10 4 cells/ml [26,27], but samples with as few as 1000 cells/ml have been reported [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the question remains unanswered as to what extent patient macrophages elicit properties and functionality of those found in health. For example, it is reported that bronchial lavage (BAL) macrophages from healthy individuals or patients with sarcoidosis, alveolar proteinosis, or malignancies differ significantly in their morphological and functional properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, although the cellular analysis of BAL fluid was not recommended for patients clinically suspected of having idiopathic pulmonary fibrosis (IPF) (14), a recent guideline suggested that a BAL fluid cellular lymphocyte analysis might play a key role in distinguishing fibrotic HP from IPF (15). Recent studies have shown new scores for discriminating between healthy and diseased individuals (16) and differentiating common variable immunodeficiencyassociated ILD from sarcoidosis (17).…”
Section: Introductionmentioning
confidence: 99%